Penerapan Metode Project-Based Learning berbantuan Video Pada Instalasi Motor Listrik - Pelita Hikmah, Fatmi; Usmeldi, Usmeldi (Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to examine student learning outcomes following the implementation of the video-assisted Project-Based Learning (PjBL) method in Class XI TITL 1 at SMK Negeri 1 Pariaman. The low level of student learning outcomes is attributed to limited engagement during the learning process. Therefore, this research investigates whether the video-assisted PjBL method can enhance student achievement. An experimental research design was employed, using a one-group pretest-posttest model. The participants were 32 students from Class XI TITL 1 at SMK Negeri 1 Pariaman during the 2024/2025 academic year. To measure learning outcomes, a pretest was administered before applying the video-assisted PjBL method, followed by a posttest after completing the learning process on the topic of Electric Motor Installation. The posttest results were analyzed using the N-Gain Score and criteria for learning mastery. The findings indicate that student scores significantly improved after the implementation of the video-assisted PjBL method. This suggests that the application of video-assisted PjBL effectively enhances student learning outcomes in the Electric Motor Installation subject at SMK Negeri 1 Pariaman.